Citizen assessment on expectation and performance among frontliners before and during the first wave of Covid-19 catastrophe / Siti Hajjar Mohd Amin ... [et al.] - Mohd Amin, Siti Hajjar; Abdullah, Aida; Mohamed Ali, Abdul Jalil; Mohd Shafie, Siti Aishah; Mohd Wahid, Siti Daleela (2021)
Numerous studies have characterised citizen happiness in various ways. Citizens' satisfaction has long been disputed in numerous situations, which might impact government and public service providers (Elrehail et al., 2019; Jilke, 2018; Li et al., 2013; Suchánek & Králová, 2018; Wang, 2010; Zenker & Rütter, 2014). Citizens may evaluate services purely for their advantage or the benefit of all users (Song et al., 2020). Expectations, experiences, and prior attitudes all play a part in citizen satisfaction. A crisis is one factor that influences citizen satisfaction (Lakovic, 2021; Venetoklis, 2021). A crisis underlines the need for comprehensive crisis preparedness and management in the public sector. Amid great uncertainty, political and administrative authorities perceive a threat to society's fundamental ideals and/or life-sustaining institutions (Rosenthal et al., 1989). Malaysia has been in shock for about two years due to political and epidemic events, with severe socio-political repercussions.